Endophy Bacterial Phenoty of Aloe Vera (Aloe barbadensis miller) as the Producer of Antibacterial Compounds Towards Eschericia coli and Staphylococcus aureus - Hildegardis Missa; Aloysius Djalo; Sardina Ndukang (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2022)
The aims of this research are to isolate endophytic bacteria in aloe vera, to determine the antibacterial ability of endophytic bacteria contained in aloe vera against the growth of Staphylococcus aureus and Escherichia coli bacteria and to determine the characterization of endophytic bacteria found in aloe vera. This research is a laboratory experimental study with research procedures, namely sampling by purposive sampling method, isolation of endophytic bacteria carried out by strake plate, antibacterial potential test against Staphylococcus aureus and Escherichia coli using paper disc diffusion method, Morphological identification was carried out by staining bacteria gram, Phenotypic characterization of endophytic bacteria using Profile matching method. The results showed that endophytic bacteria found in aloe vera leaves were characterized by the growth of bacterial colonies on Murashige-Skoog (MS) media with different shapes and colors, the results of the antibacterial potential of endophytes against the growth of Escherichia coli and Staphylococcus aureus showed that there were 6 bacterial isolates that showed clear zones in Escherichia coli and Staphylococcus aureus bacteria and characterization results showed that isolates H2L, H9L and H10L had similar genera to Staphylococcus and Bacillus while isolates H4L, H5L and H7L had similar genera to Pseudomonas.